Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1371/journal.pone.0178823
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative serum cystatin-C as a potential biomarker for prognosis of renal cell carcinoma

Abstract: PurposeThe prognostic value of serum cystatin-C (Cys-C) in renal cell carcinoma (RCC) remains unknown. The purpose of this study is to explore the prognostic value of Cys-C for RCC patients.Patients and methodsThe levels of preoperative Cys-C, creatinine (CRE) and estimated glomerular filtration rate (e-GFR) were retrospectively collected in 325 RCC patients undergoing surgery. The cutoff values of Cys-C, CRE and e-GFR were determined by the standardized Cutoff Finder algorithm. The receiver operating characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 43 publications
2
29
0
Order By: Relevance
“…33 The same group showed that elevated preoperative CST3 serum levels were associated with poor survival in RCC. 34 This aligns with our study as patients with elevated CST3 expression had significantly worse OS. Another study found that HSPE1 expression was significantly downregulated in ccRCC tissues compared to adjacent normal kidney tissues.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…33 The same group showed that elevated preoperative CST3 serum levels were associated with poor survival in RCC. 34 This aligns with our study as patients with elevated CST3 expression had significantly worse OS. Another study found that HSPE1 expression was significantly downregulated in ccRCC tissues compared to adjacent normal kidney tissues.…”
Section: Discussionsupporting
confidence: 91%
“…Recently, elevated CST3 expression was found to be associated with poor prognosis in ccRCC . The same group showed that elevated preoperative CST3 serum levels were associated with poor survival in RCC . This aligns with our study as patients with elevated CST3 expression had significantly worse OS.…”
Section: Discussionsupporting
confidence: 90%
“…The association between chronic inflammation and cancer are duplex, inflammation can induce tumorigenesis and metastasis by affect cell proliferation, death, and angiogenesis through elevate the levels of cytokines, nuclear factor κB (NF-κB), prostaglandins and micro RNAs.et al, tumors also can induce inflammatory reactions through express cytokines that recruit neutrophils and macrophages [24] . Recent study have indicated that NLR is an indicator of systemic inflammation and general immune response of the cancer [25,26] . Although there are some other systemic inflammation reaction biomarkers, such as CRP , cystatin-C and PLR , were reported to be used for prognostic indexes in RCC [9][27] .…”
Section: Discussionmentioning
confidence: 99%
“…As a member of cysteine protease inhibitors, Cystatin C also inhibits tumor invasion and metastasis 17 .…”
Section: Prognostic Toolmentioning
confidence: 99%
“…An elevated preoperative Cystatin C level was demonstrated to be related with worse survival in patients with renal cell carcinoma. Measuring preoperative serum Cystatin C seems to be an effortless way for finding poor prognostic patients and patients with elevated preoperative Cystatin C level should be more closely followed up 17 .…”
Section: Prognostic Toolmentioning
confidence: 99%